Genetic Polymorphism of Mismatch Repair Genes and Susceptibility to Prostate Cancer - Khooshemehri, Paniz; Jamaldini, Seyed Hamid; Ziaee, Seyed Amir Mohsen; Afshari, Mahdi; Sattari, Mahshid; Narouie, Behzad; Sotoudeh, Mehdi; Montazeri, Vahideh; Sarhangi, Negar; Hasanzad, Mandana (Urology Journal, 2020)
Purpose: Mismatch repair (MMR) is one of the DNA repair systems that correct mispaired bases during DNA replication errors. Polymorphisms in genes can increase susceptibility to the development of prostate cancer (PCa). In this study, we investigated mutL homolog 1 (MLH1) -93G>A (rs1800734) and mutS homolog 3 (MSH3) (rs26279) polymorphisms with the risk of PCa. Materials and Methods: In this study of Iranian population, 175 histopathologically confirmed (PCa) patients and 230 benign prostate hyperplasia (BPH) as the controls were recruited. The genotypes of MLH1 and MSH3 were determined by polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP) method. Results: There was no significant difference of MLH1 (P = 0.4) and MSH3 (P?=?0.5) genotype distributions among PCa cases and controls. And also patients with PCa were not significant differences compared to those without in stage of cancer, grade of tumor, perineural invasion, and vascular invasion. Conclusion: Our results did not show adequate evidence for any significant association of MLH1 and MSH3 polymorphisms and PCa .